2016
DOI: 10.5603/ep.2016.0068
|View full text |Cite
|
Sign up to set email alerts
|

Wpływ występowania allelu klasy III VNTR genu INS na parametry auksologiczne, stężenie glukozy, insuliny, lipidów i adipocytokin u przeddojrzewaniowych dzieci urodzonych z niską masą ciała

Abstract: Introduction:The insulin gene variable number of tandem repeats (INS VNTR) class III allele has been implicated in lower birth weight, obesity, and insulin resistance. We assessed its influence on birth weight in the Polish population and on the current body mass and metabolic profile in prepubertal children born small for gestational age (SGA). Material and methods: DNA for genotyping of INS VNTR was available for 123 subjects born SGA and 132 born appropriate for gestational age (AGA). We identified two alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…SOCS3, JAK2, STAT3, and LEPRB in module 3 ( Figure 8(b) ) are components of the JAK2-STAT3 pathway. Reportedly, INS and LEP are closely related to obesity [ 19 , 20 ], while PTPN11 was identified in the studies of histiocytic sarcoma and Noonan syndrome [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…SOCS3, JAK2, STAT3, and LEPRB in module 3 ( Figure 8(b) ) are components of the JAK2-STAT3 pathway. Reportedly, INS and LEP are closely related to obesity [ 19 , 20 ], while PTPN11 was identified in the studies of histiocytic sarcoma and Noonan syndrome [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that ketosis in dairy cows is caused by negative energy balance (NEB), the disorder in glucose and lipid metabolism, high concentration of non-esterified fatty acid (NEFA), β-hydroxybutyric acid (BHBA), and insulin resistance (IR) (Li et al 2014, Ježek et al 2017. Adipokines regulate oxidative stress, inflammatory response and energy balance by influencing insulin sensitivity and regulating glucose and lipid metabolism (Yu-Duan et al 2013, Stawerska et al 2016, indicating that NEB is closely associated with ketosis in dairy cows. Recently, researchers found that adiponectin (ADP) and leptin (LEP) play important roles in regulation of energy balance, INS sensitivity and appetite (López-Jaramillo et al 2014).…”
Section: Introductionmentioning
confidence: 99%